1990
DOI: 10.1038/346269a0
|View full text |Cite
|
Sign up to set email alerts
|

Suppression by glutamate of cGMP-activated conductance in retinal bipolar cells

Abstract: Depolarizing bipolar cells (DBCs) of the retina are the only neurons in the vertebrate central nervous system known to be hyperpolarized by the neurotransmitter glutamate. Both glutamate and its analogue L-2-amino-4-phosphonobutyrate (APB) hyperpolarize DBCs by decreasing membrane conductance. Furthermore, glutamate responses in DBCs slowly decrease during whole-cell recording, suggesting that the response involves a second messenger system. Here we report that intracellular cyclic GMP or GTP activates a membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
235
1
2

Year Published

1996
1996
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 437 publications
(249 citation statements)
references
References 22 publications
11
235
1
2
Order By: Relevance
“…In fact, quantal miniature EPSCs have been detected in OFF bipolar cells and uncoupled horizontal cells (Hirasawa et al, 2001a;Kawai, 1999;Maple et al, 1994). Noise analysis also suggests an underlying quantal structure to ON bipolar cell responses , although discrete miniature EPSCs in this cell type are obscured by the slow kinetics of the mGluR6 transduction cascade (Nawy and Jahr, 1990). …”
Section: Do Post-synaptic Responses Conform To the Quantal Hypothesis?mentioning
confidence: 99%
“…In fact, quantal miniature EPSCs have been detected in OFF bipolar cells and uncoupled horizontal cells (Hirasawa et al, 2001a;Kawai, 1999;Maple et al, 1994). Noise analysis also suggests an underlying quantal structure to ON bipolar cell responses , although discrete miniature EPSCs in this cell type are obscured by the slow kinetics of the mGluR6 transduction cascade (Nawy and Jahr, 1990). …”
Section: Do Post-synaptic Responses Conform To the Quantal Hypothesis?mentioning
confidence: 99%
“…Early studies of the glutamate receptor expressed by ON bipolar cells in lower vertebrates revealed that it possessed a novel pharmacological profile, as it was activated by L-2-amino-4-phosphonobutyric acid (L-AP4), and that activation of the receptor was associated with a conductance decrease (Shiells et al, 1981;Slaughter and Miller, 1981). Measurements of the current-voltage relation associated with the response to L-AP4 and to light demonstrated that both L-AP4 and the endogenous photoreceptor transmitter closed a channel with a reversal potential near 0 mV (Nawy and Copenhagen, 1987;Nawy and Jahr, 1990a). Furthermore, patch clamp experiments in which GTP analogs were dialyzed into ON bipolar cells demonstrated that the as yet unidentified receptor operated via a G protein-coupled mechanism (Nawy and Jahr, 1990a).…”
Section: The Mglur6 Receptor and Its Signaling Pathwaymentioning
confidence: 99%
“…Measurements of the current-voltage relation associated with the response to L-AP4 and to light demonstrated that both L-AP4 and the endogenous photoreceptor transmitter closed a channel with a reversal potential near 0 mV (Nawy and Copenhagen, 1987;Nawy and Jahr, 1990a). Furthermore, patch clamp experiments in which GTP analogs were dialyzed into ON bipolar cells demonstrated that the as yet unidentified receptor operated via a G protein-coupled mechanism (Nawy and Jahr, 1990a). Several years later, the receptor was cloned and termed mGluR6 (Nakajima et al, 1993), a member of the group III family of metabotropic glutamate receptors.…”
Section: The Mglur6 Receptor and Its Signaling Pathwaymentioning
confidence: 99%
“…Therefore, we asked whether CB3a and CB3b could represent two subtypes of CBCs with opposite light response polarity. To address this question, we first examined their responses to L-AP4 (Slaughter & Miller 1981;Nawy & Jahr, 1990). Application of L-AP4 (50 μM) was found to reduce the steady inward current in both CB3a (n = 4) and CB3b (n = 7) ( Figures 5A and B), suggesting that metabotropic glutamate receptors are present in both groups of CBCs.…”
Section: The Presence Of a Second Subclass Of Cb3 That Does Not Exprementioning
confidence: 99%